The role of a support person during labour - Katarzyna Anna Bojarczuk; Agnieszka Łagowska-Batyra; Maciej Kochman; Magdalena Michalczak; Agata Smoleń (Kazimierz Wielki University, 2018)
Introduction: The changes that have occurred in the obstetrics in the last years are not only culturally conditioned, but they also constitute the sum of experiences of many generations of the women in labour. The change of a labour management style and the partner's presence at that time is the result of variable expectations of women as well as the courage and determination of representatives of medical professions. When both partners are aware and active during the labour, a mother has the comfort of giving a birth in the sense of safety, and the father feels the full acceptance of a child as it eliminates the fear of physical contact with a baby. Objectives: The objective of this work is to know the opinion of women about the support person during labour. Materials and methods: The anonymous surveys were used as the research method. The study involved 187 women in labour, after the family labour in the average age of 29 ± 10 years. It was directed at the women after the family labour to know their opinion about the role of a support person during labour. Results: The conducted analysis has proved that the couples make decision together as to the family labour 59.4%. The factors that influence on this decision are the following to stay together (53.5%) and to provide the sense of safety (38.5%). According to 87.7% of the surveyed, the major type of the partner's activity during the labour was his emotional support. 90.9% of the women confirm their partner would participate during the another labour again. Conclusions: 1.The decision about the family labour is made together by both partners. 2.Because of the partner's presence during a labour, there are more chances for the better relationship of a man with his child in the future. 3.The major motivation for the man's presence during the labour is to provide the sense of safety to his woman in labour.